Elderly with oral diseases and antihypertensive medication - Lian Cristino Nuñez Peña; Ana Ibis Bosch Núñez; Liuba González Espangler; Yurima Trupman Hernández (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: The consumption of antihypertensive medications is related to the emergence of multiple oral diseases in the elderly. Objective: To characterize the elderly with oral diseases and antihypertensive medication. Methods: An observational, descriptive and cross-sectional investigation was carried out of 79 elderly with oral diseases and antihypertensive medication, assisted in the Stomatology Service of 14 de Junio Polyclinic, in Las Tunas province, from January, 2021 to the same month in 2022. Among the analyzed variables we can mention: age, sex, consumed medication (according to antihypertensive group) and presence of oral disease. Theoretical methods (analytic-synthetic and inductive-deductive), empiric (observation and surveys) and statistical (descriptive statistic) were used.  The percentage was used as summary measure.  Results: In the series there was prevalence of the female sex (63.3 %) and the 60-69 age group (48.1 %). It was observed that the most used antihypertensive groups were the thiazidic diuretics, angiotensin-converting enzyme inhibitor and blocker of the calcium channels; among these, the most consumed medications were hydrochlorothiazide (90.0 %), captopril (47.0 %) and nifedipine (20.0 %), respectively. Also, when analyzing the presence of oral diseases a primacy of dental decay (90.0 %), periodontopaties (87.3 %) and xerostomia was obtained (57.0 %).  Conclusions: Elderly with oral diseases and antihypertensive medication, in particular females and the 60-69 age group were characterized by the consumption of first generation antihypertensive drugs and the presence of frequent oral diseases.